Dinamika Masyarakat Eropa dan Globalisasi Politik: Perspektif Kajian Wilayah - Dr Siswanto (Jurnal Kajian Wilayah, 2014)
This paper is intended as an attempt to understand the dynamics of European society, related to the issue of globalization, in particular the issue of political globalization. Globalization in political issues in Europe caused to the Democratization of Eastern Europe. Before the wave of democratization, Eastern Europe is the Communist political order and after that into a liberal democracy. The problem is how to learn from the process of political globalization in the region properly. The approach used in this paper is the analysis of the facts and inter-disciplinary study. Achieved the result is an understanding that the event democratization in Eastern Europe is valuable lessons for the nations of the World and the conclusion is that occurred democratization in Eastern Europe should became the reference of the process of Indonesia reform.